2018
DOI: 10.1186/s12936-018-2574-0
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian spatiotemporal analysis of malaria infection along an international border: Hlaingbwe Township in Myanmar and Tha-Song-Yang District in Thailand

Abstract: BackgroundOne challenge in moving towards malaria elimination is cross-border malaria infection. The implemented measures to prevent and control malaria re-introduction across the demarcation line between two countries require intensive analyses and interpretation of data from both sides, particularly in border areas, to make correct and timely decisions. Reliable maps of projected malaria distribution can help to direct intervention strategies. In this study, a Bayesian spatiotemporal analytic model was propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…This study further extrapolates this notion in perspective of its potential contribution to transmission of the non- falciparum species at the border areas of Zambia with the two neighbouring countries. All conditions permitting, this is a possibility as one study suggests that individuals who enter malaria regions can influence epidemiological dynamics [ 52 ]. It is necessary to study further the transmission potential that could exist with the presence of species other than P. falciparum and their gametocytes, as part of the process for planning and revising of control and elimination efforts.…”
Section: Discussionmentioning
confidence: 99%
“…This study further extrapolates this notion in perspective of its potential contribution to transmission of the non- falciparum species at the border areas of Zambia with the two neighbouring countries. All conditions permitting, this is a possibility as one study suggests that individuals who enter malaria regions can influence epidemiological dynamics [ 52 ]. It is necessary to study further the transmission potential that could exist with the presence of species other than P. falciparum and their gametocytes, as part of the process for planning and revising of control and elimination efforts.…”
Section: Discussionmentioning
confidence: 99%
“…The Besag, York, and Mollie (BYM) model was used to model the common spatial component [24], which consisted of two components: spatially structured random effect μi and spatially unstructured random effect υi. μi was commonly assumed to follow a conditional autoregressive prior structure (CAR) in infectious diseases spatial epidemiology [25,26,27], which showed that county i had a similar pattern of disease incidence with the adjacent counties. υi was assumed to be a normal distribution, representing that county i had an independent pattern of disease incidence from the adjacent counties.…”
Section: Methodsmentioning
confidence: 99%
“… 16 Another study used epidemiology and surveillance data to develop and calculate risk factor coefficients via a Bayesian spatial negative binomial model and subsequently used the model-based relative risk estimates to map malaria risk areas. 17 Multi-criteria decision analysis (MCDA) is a decision support tool that allows for the consideration of diverse quantitative and qualitative criteria using both data-driven and qualitative indicators from stakeholder participations. 4 Multi-criteria decision analysis was initiated in the field of operation research and subsequently has been applied to many disciplines, including environmental, agricultural, transportation, and urban planning, and recently has been applied in public health.…”
Section: Introductionmentioning
confidence: 99%